2001
DOI: 10.1023/a:1011125220522
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of PTSD symptom severity and social reactions in sexual assault victims

Abstract: Demographics, assault variables, and postassault responses were analyzed as correlates of PTSD symptom severity in a sample of 323 sexual assault victims. Regression analyses indicated that less education, greater perceived life threat, and receipt of more negative social reactions upon disclosing assault were each related to greater PTSD symptom severity. Ethnic minority victims reported more negative social reactions from others. Victims of more severe sexual victimization reported fewer positive, but more n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
376
1
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(435 citation statements)
references
References 44 publications
(55 reference statements)
40
376
1
13
Order By: Relevance
“…In this study, we also found in MS patients a significant relationship between PTSD and the level of education, previously found in other clinical populations (Vasterling et al, 2002;Ullman and Filipas, 2001). At this point in time, no clear explanation for this finding exists, so it is only possible to speculate about it.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, we also found in MS patients a significant relationship between PTSD and the level of education, previously found in other clinical populations (Vasterling et al, 2002;Ullman and Filipas, 2001). At this point in time, no clear explanation for this finding exists, so it is only possible to speculate about it.…”
Section: Discussionsupporting
confidence: 52%
“…Rape disclosure receipt is a relatively common phenomenon, with approximately 20-40% of college students (Banyard, Moynihan, Walsh, Cohn, & Ward, 2010; and 35% of women in a national sample (Paul et al, 2014) reporting this experience. Despite the support and services that disclosure may yield for to victims (e.g., Ahrens et al, 2007;Ullman, 2010;Ullman & Filipas, 2001), it is well-documented that negative reactions to disclosure lead to greater victim self-blame (Ullman, 1996), adverse mental health outcomes (Davis, Brickman, & Baker, 1991;Ullman & Filipas, 2001), and a decreased likelihood of reporting the assault to police (Ahrens, 2006). If the label given to an act of sexual violence by the victim or the disclosure recipient leads to a negative reaction (e.g., minimized severity of the assault), or if such a response is engendered by inconsistencies between the label assigned by the victim and how it is interpreted by the recipient, victim outcomes may be adversely affected.…”
Section: Labeling Sexual Violencementioning
confidence: 99%
“…Review of studies from 19 countries showed that prevalence rates for women may vary from 7% to 36% (Finklehor, 1994). Many women who were exposed to child sexual abuse develop serious psychopathology, including depression, borderline personality disorder, and posttraumatic stress disorder (Bulik, Prescott, & Kendler, 2001;Molnar, Buka, & Kessler, 2001;Ullman & Filipas, 2001;Zanarini et al, 2002).…”
Section: Studymentioning
confidence: 99%